Сравнительное изучение синдрома «Burnout» в профессиональных группах напряженного труда – авиа-диспетчеров и инженерно-технических работников радиотехнического обеспечения управления воздушным движением - Пышнов, Г.Ю.; Высоцкая, Л.Г. (Актуальні проблеми транспортної медицини, 2005)
Проведені дослідження на групі авіадиспетчерів аеропорту «Бориспіль» та інженерів-електроників радіолокації, радіонавігації і зв'язку дозволили виявити наявність синдрому «вигоряння» і порівняти структурні складові синдрому в цих професійних групах. Визначено структуру синдрому, частота спостередження у вибірці і позначені ведучі симптоми у фазах синдрому. Виявлено залежність ступеня формування синдрому «вигоряння» від стажу роботи в даних професіях. Ключові слова: напружена праця, синдром «вигоряння» чи «burnout», порушення адаптації, авіадиспетчери, інженери радіолокації, радіонавігації і зв'язку. The trials have been carried out in the groups of air traffic controllers and electronic engineers of radiolocation, radionavigation and communication of the airport "Borispol". The presence of "burnout" syndrome has been revealed in the both groups under study. They have learnt its structure, prevalence and leading symptoms in comparison with the named syndrome phases. The link between "burnout" syndrome formation and length of service at the named capacities has been revealed. Key words: intense work, syndrome of «burnout», infringement of adaptation, airdispatchers, engineers of a radar-location, radionavigation and communication.